2011
DOI: 10.1038/nn.2970
|View full text |Cite
|
Sign up to set email alerts
|

UNC-33 (CRMP) and ankyrin organize microtubules and localize kinesin to polarize axon-dendrite sorting

Abstract: The polarized distribution of neuronal proteins to axons and dendrites relies upon microtubule-binding proteins such as CRMP, directed motors such as kinesin UNC-104/Kif1A, and diffusion barriers such as ankyrin. The causative relationships between these molecules are unknown. We show here that Caenorhabditis elegans CRMP (UNC-33) acts early in neuronal development, together with ankyrin (UNC-44), to organize microtubule asymmetry and axon-dendrite sorting. In unc-33 and unc-44 mutants, axonal proteins are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
184
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(211 citation statements)
references
References 49 publications
25
184
2
Order By: Relevance
“…In C. elegans neurons, including cholinergic motor neurons, microtubules in the axon are oriented with their plus ends out (i.e., toward the synaptic region), whereas microtubules in the dendrite are predominantly oriented with their minus ends out (Goodwin et al 2012;Maniar et al 2012;Yan et al 2013). found that eliminating the cyclindependent kinase pathways CDK-5 (cyclin-dependent kinase 5) and PCT-1 (Pctaire kinase) in the DA9 motor neuron causes a redistribution of SVs from the synaptic region to the cell soma and dendrite similar to unc-104 loss-of-function mutants and that this redistribution requires components of the dynein minus-end-directed motor complex, such as DHC-1 (dynein heavy chain) and NUD-2 (known as NUDEL in vertebrates).…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans neurons, including cholinergic motor neurons, microtubules in the axon are oriented with their plus ends out (i.e., toward the synaptic region), whereas microtubules in the dendrite are predominantly oriented with their minus ends out (Goodwin et al 2012;Maniar et al 2012;Yan et al 2013). found that eliminating the cyclindependent kinase pathways CDK-5 (cyclin-dependent kinase 5) and PCT-1 (Pctaire kinase) in the DA9 motor neuron causes a redistribution of SVs from the synaptic region to the cell soma and dendrite similar to unc-104 loss-of-function mutants and that this redistribution requires components of the dynein minus-end-directed motor complex, such as DHC-1 (dynein heavy chain) and NUD-2 (known as NUDEL in vertebrates).…”
Section: Resultsmentioning
confidence: 99%
“…The mild phenotype in fln-1(tm545) mutant may be due to the limited contribution of FLN-1 in DD/VD projection and/or the compensation by the other filamin isoform in C. elegans, FLN-2. The severe abnormal phenotype in unc-33 mutants may reflect the insufficient regulation of tubulin assembly 6 and/or the polarized defect 8 . fln-1(tm545) enhanced the phenotype of weak allele mutant unc-33(e204) (Fig.…”
Section: Crmp1 Regulates the Interaction Of Filamin-a And F-actinmentioning
confidence: 99%
“…CRMPs share significant homology with UNC-33 in Caenorhabditis elegans 5 . UNC-33 is involved in the axonal outgrowth and guidance of various neurons through the regulation of tubulin dynamics and neuronal polarity in nematodes [6][7][8] .…”
mentioning
confidence: 99%
“…1A) (Oren-Suissa et al, 2010). These dendritic trees arise and are dynamically maintained through several intrinsic and extrinsic genetic pathways (Chatzigeorgiou et al, 2010;Cohen et al, 2014;Dong et al, 2013Dong et al, , 2015Husson et al, 2012;Liu and Shen, 2011;Maniar et al, 2012;Oren-Suissa et al, 2010;Salzberg et al, 2013;Smith et al, 2010;Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%